2022
DOI: 10.3390/ijerph19084660
|View full text |Cite
|
Sign up to set email alerts
|

Rotaviruses and Noroviruses as Etiological Agents of Acute Intestinal Diseases of Ukrainian Children

Abstract: (1) Background: Rotavirus and norovirus infections are the primary viral causes of childhood diarrhea. In Ukraine, the diarrhea-linked infant mortality rate is low, but the number of children infected is quite high. This study examined the rates of rotavirus and norovirus infections throughout Ukraine. (2) Methods: Fecal samples for children admitted to hospitals in six Ukrainian cities (Kyiv, Lviv, Sumy, Odesa, Kharkiv, and Uman) were tested for the presence of rotavirus and norovirus. (3) Results: The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…21,22 In both Poland and Ukraine, RV gastroenteritis prevalence peaks in winter months. 20,21 RV gastroenteritis is characterized by 3 basic symptoms: fever, vomiting and diarrhea, which were also common in our patients. 20 Importantly, children in our series presented with a particularly severe course of gastroenteritis, with prolonged lethargy despite appropriate treatment.…”
Section: Epidemiologic Circumstancesmentioning
confidence: 57%
See 2 more Smart Citations
“…21,22 In both Poland and Ukraine, RV gastroenteritis prevalence peaks in winter months. 20,21 RV gastroenteritis is characterized by 3 basic symptoms: fever, vomiting and diarrhea, which were also common in our patients. 20 Importantly, children in our series presented with a particularly severe course of gastroenteritis, with prolonged lethargy despite appropriate treatment.…”
Section: Epidemiologic Circumstancesmentioning
confidence: 57%
“…RV gastroenteritis is characterized by 3 basic symptoms: fever, vomiting and diarrhea, which were also common in our patients. 20 Importantly, children in our series presented with a particularly severe course of gastroenteritis, with prolonged lethargy despite appropriate treatment. This is in line with European studies, which showed that RV gastroenteritis is more severe than gastroenteritis caused by other viruses.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Не менш важливою проблемою залишаються інфекції шлунково-кишкового тракту, зокрема вірусні гастроентерити, етіологічними агентами яких є ротавіруси, норовіруси, кишкові аденовіруси, астровіруси. Вірусні гастроентерити особливо вражають дітей до п'яти років [4]. Наразі відсутні препарати етіотропної дії, які можуть бути ефективними для лікування вірусних гастроентеритів, тому актуальною залишається комбінована симптоматична та патогенетична те-рапія як для дітей, так і для дорослих [5,6].…”
Section: вступunclassified